Order Specification Management: evaluation and path to improvement - Alatalo, Miika (My University, 2024)
The contemporary market puts continually growing pressure on firms to deliver products with no defects, brief lead times, and rapid design turns. These requirements are particularly challenging for engineer-to-order firms who must discover how to evaluate product design, find out tooling requirements, finish process designs, and deliver items on schedule. In engineer-to-order companies’ sales-delivery process there is a possibility to utilize design reuse while creating new product variations which leads to decreased customer-specific design costs and shorter lead times. Order Specification Management (OSM) was developed by the case company to increase productivity in project management. It is mainly used for creating, updating, and deleting purchase order requisitions. The purpose of this thesis is to get an objective perception of the application’s current state by interviewing both developers and users. The objective is to get answers to three research questions: 1) How can lean principles, product configurators, and product lifecycle management improve efficiency in engineer-to-order companies? 2) What benefits have been sought originally by implementing OSM and what is the current state of the system? 3) Is Order Specification Management fit for purpose for case company? Theoretical topics that are covered in this thesis include lean, engineer-to-order, product configurators, and product lifecycle management. Research method used in this thesis is qualitative case study. For data collection interviews and a questionnaire are used. In addition, the case company’s internal documents are used as a secondary data. The interviews with developers revealed that the purpose of developing OSM was to make project engineers’ work easier and make it possible to reuse the existing data. The results of the study indicate that developers and users have different opinions about the application. All the interviewed developers thought that OSM is working as it is supposed to whereas the users thought that there is room for improvement in the usability of the application. OSM received criticism especially about its slowness and poor data quality. However, the participants of the focused interview recognized also positive things about OSM, such as its ability to see more details about products compared to SAP. Furthermore, when using OSM there is no need to copy data from several documents and places.

Tämän päivän markkinat asettavat yrityksille jatkuvasti enemmän paineita toimittaa tuotteita ilman vikoja, lyhyemmillä toimitusajoilla ja nopeammilla suunnittelun käänteillä. Nämä vaatimukset aiheuttavat haasteita erityisesti yrityksille, joiden tuotantomuoto on tilauksesta suunnittelu. Näiden yritysten täytyy arvioida tuotteen suunnittelua, selvittää työkaluvaatimukset, viimeistellä prosessisuunnitelmat sekä toimittaa tuotteet aikataulussa. Tilauksesta suunnittelevien firmojen myynti-toimitusprosessissa on mahdollisuus hyödyntää vanhoja suunnitteluratkaisuja uusien tuotevariaatioiden luomisessa, jolloin asiakaskohtaiset suunnittelukustannukset laskevat ja läpimenoajat lyhenevät. Order Specification Management (OSM) sovellus kehitettiin tapausyritykselle lisäämään tuottavuutta projektin hallinnassa. Sitä käytetään pääasiassa ostotilauspyyntöjen luomiseen, päivittämiseen ja poistamiseen. Tutkielman tarkoituksena on saada objektiivinen käsitys sovelluksen nykytilasta haastattelemalla sekä sovelluksen kehittäjiä, että sen käyttäjiä. Tavoitteena on saada vastaus kolmeen tutkimuskysymykseen: 1) Miten lean periaatteet, tuotekonfiguraattorit ja tuotteen elinkaaren hallinta voivat parantaa tehokkuutta tilauksesta suunnittelevien yritysten toiminnassa? 2) Mitä hyötyjä OSM sovelluksella on alun perin tavoiteltu ja mikä on sovelluksen nykytila? 3) Onko OSM tarkoitukseen sopiva kohdeyritykselle? Teoriaosuudessa käsiteltävät aiheet ovat lean, tilauksesta suunnittelu, tuotekonfiguraattorit ja tuotteen elinkaaren hallinta. Tutkielmassa käytetty tutkimusmenetelmä on laadullinen tapaustutkimus. Tutkielman tiedonkeruussa on käytetty haastatteluja sekä kyselyä. Lisäksi kohdeyrityksen sisäisiä dokumentteja on käytetty tutkielmassa toissijaisena aineistona. Kehittäjien kanssa tehdyissä haastatteluissa selvisi, että OSM:n kehittämisellä pyrittiin helpottamaan projekti-insinöörien työtä sekä mahdollistamaan olemassa olevan datan uudelleen käyttämistä. Tutkimuksen tulokset osoittavat, että OSM:n kehittäjillä ja käyttäjillä on eriäviä mielipiteitä sovelluksesta. Kaikki haastatellut kehittäjät olivat sitä mieltä, että OSM toimii sille tarkoitetulla tavalla, kun taas käyttäjät arvioivat sovelluksen käytettävyydessä olevan parantamisen varaa. OSM sai kritiikkiä erityisesti hitaudestaan sekä heikosta datan laadusta. Teemahaastattelun osallistujat tunnistivat kuitenkin myös positiivisia asioita OSM:stä kuten, että sen avulla näkee enemmän yksityiskohtia tuotteesta kuin SAP:ta käyttämällä. Lisäksi OSM:ää käyttämällä ei tarvitse kopioida tietoja monista eri dokumenteista ja paikoista.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management